Oral Glutamine Supplementation Benefits Jejunum but Not Ileum - Paul E Hardy; Karen L Madsen; Olin G Thurston; Stewart M Hamilton; Ningren Cui; Richard N Fedorak (Canadian Journal of Gastroenterology)
Glutamine is the primary metabolic fuel of the small intestine. The ability of enteral glutamine to support jejunal architecture and metabolism is well established, but its effect on intestinal absorptive function, especially in the terminal ileum, remains undetermined. The purpose of this study was to develop a functional ileal fluid absorption surgical injury model and to determine if oral glutamine supplementation would be beneficial in accelerating healing and restoring function. The effects of either 1 cm resection and ileal end-to-end anastomosis or sham laparotomy on rat in vivo fluid absorption at study start (day 0), one and two days was investigated. In sham-operated rats, fluid absorption was not altered. In contrast, ileal fluid absorption was significantly reduced at days 0 (17.2±4.8 μL/cm/h) and 1 (31.4±13.6 μL/cm/h), but returned to normal by day 2 (71.0±6.2 μL/cm/h) in anastomosed rats. To examine the effects of glutamine in this model, rats were fed either glutamine (2.4 g/kg/day) or an isonitrogenous glycine-supplemented elemental oral diet for five days before their randomization to sham or anastomotic groups. This dose of glutamine reached the ileum and was completely absorbed along the small intestine. Glutamine-fed rats demonstrated no difference in recovery of in vivo ileal fluid absorption, ileal villus morphometric measurements, mg DNA:mg protein ratio, degree of inflammation or glutaminase activity. In contrast, jejunal, but not ileal, villus morphometry, mg DNA:mg protein ratio and glutaminase activity were increased in glutamine-fed ‘not operated’ rats (P<0.01), indicating that the jejunum, but not the ileum, responded to the glutamine-supplemented diet. These studies demonstrate that ileal resection and anastomosis causes transient impairments in in vivo fluid absorption, and oral glutamine supplementation offers a beneficial effect to jejunal, but not ileal, intestinal mucosa. These results suggest that the effects of oral glutamine may be limited to the proximal intestine.